On liveness: using arts workshops as a research method. (February 2018) - Tarr, Jen; Gonzalez-Polledo, Elena; Cornish, Flora
Drawing on a research project using arts workshops to explore pain communication, we develop a methodological reflection on the significance of the liveness of arts-based methods. We discuss how liveness informed the design of workshops to provoke novel forms of communication; how it produced uncontrollable and unpredictable workshops, whose unfolding we theorize as 'imprography'. It also constituted affective and collective experiences of 'being there' as important but difficult-to-record parts of the data, which raises challenges to current understandings of what constitutes data, particularly in the context of team research and in light of directives for archiving and reuse. We explore the implications of liveness for methodological practice.